Occupational therapy performance, participation, and well-being - Julie D. Bass; Carolyn Manville Baum; Charles Christiansen (SLACK Incorporated, 2015)
Occupational Therapy: Performance, Participation, and Well-Being, Fourth Edition, is a comprehensive occupational therapy text that introduces students to core knowledge in the profession and the foundations of practice--the occupations, person factors, and environment factors that support performance, participation, and well-being. Editors, Drs. Charles H. Christiansen, Carolyn M. Baum, and Julie D. Bass, are joined by more than 40 international scholars who bring students, faculty, and practitioners the evidence that supports occupational therapy practice. The PEOP Model 4th Edition is featured as an exemplar of a person-environment-occupation model and provides a valuable roadmap for understanding key concepts and developing strong clinical reasoning skills in the occupational therapy process"--